Real world evidence for European health policy-making: making the case for interoperability. (13th November 2019) - Bernal-Delgado, E; Estupiñán-Romero, F; Zeynep, O; Lyons, R; Ivanković, D
Abstract: Background: The foundations of evidence-based health policy-making are transitioning from the use of partial evidence yielded elsewhere and the application of heuristic rules, to the development of learning systems based on the reuse of routine data collected by the same institutions that have to implement those policies. Supporting that transition, the scientific production of real-world evidence (RWE) is becoming pivotal, particularly in international policy-making. However, leveraging the immense wealth of data curated in European public institutions, requires the development of a new world-class research infrastructure and a supporting interoperability framework (IOF). Methods: Based on the European Interoperability Framework (EIF) legal, organizational, semantic, and technical issues are being assessed. While legal, organizational and technical topics are analyzed from the perspective of the type of infrastructure, centralized or federated, to be developed, semantic interoperability is explored using three case studies on the linkage of different real world data sources: for characterizing resilient populations, studying the burden of dementia, and the effectiveness of stroke care pathways. Results: Preliminary assessments advocate for the development of a federated infrastructure where data remain in house and research questions, data access and interoperability services are shared according to the capacity of each specific partner in the federation. Interoperability services for such an infrastructure should cover: a) the development and maintenance of a common data model to assure semantic interoperability, b) the development of self-contained distributed analytical pipelines; and c) the implementation of a training program aimed at increasing the capacity of each RI hub. Conclusions: An interoperable federated research infrastructure is required to leverage the potential of real world data for European health policy-making. InfAct is paving the way.